Odpowiedzi

Najlepsza Odpowiedź!
2010-02-09T16:14:21+01:00
A) a+( a - b)=a+a-b=2a-b

b) 2x- (x + 4)=2x-x-4=x-4

c) 7-(-x + 6)=7+x-6=x+1

d) -(x + 4) + (x - 5 ) =-x-4+x-5=-9

e) 1 - (t + p) - (t - 2 )=1-t-p-t+2=-2t-p+3

f) -(- y +2) + (-2y - 4 )=y-2-2y-4=-y-6
1 5 1
2010-02-09T16:15:00+01:00
A) a+a-b
b) 2x-x-4
c) 7+x-6
d) -x-4+x-5
e) 1-t-p-t+2
f) y+2-2y-4
2010-02-09T16:16:10+01:00
A) a+( a - b)= a +a - b= 2a-b

b) 2x- (x + 4)=2x-x-4= -4

c) 7-(-x + 6)=7+x-6=1+x

d) -(x + 4) + (x - 5 ) =-x-4+x-5= -9

e) 1 - (t + p) - (t - 2 )=1-t-p-t+2= 3-2t-p

f) -(- y +2) + (-2y - 4 )= y-2-2y-4= -y -6